Development of load carrying and releasing system of hexacopter - Zakaria, Abdul Hafiz; Mohd Mustafah, Yasir; Mohd. Hatta, Muhd. Mudzakkir; N. Azlan, Muhd Nadzif (IEEE, 2015)
An unmanned aerial vehicle (UAV) which is integrated with the gripper system is be able to provide diverse service to the society. The objective of this project is to develop a load carrying and releasing system for hexacopter platform. The proposed method is to use the hexacopter with high payload capable of flying while carrying some extra load. A gripper system with the ability to hold and release the preloaded object is designed to enable the hexacopter to transport objects. The load carrying and releasing system releases the object after receiving an instruction from the user. During the flight, mission planner is used to monitor the flight status. The hexacopter performance was evaluated through a series of flight tests. The result from the experiments show that the total flight time of the hexacopter reduced by 5 minutes from the normal time of 15 minutes when the load carrying mechanism is attached. This is because attaching the mechanism increases the total payload by 800grams from the normal payload of 2.2kg. Payload increment means higher current drawn from the battery to produce higher motor speed. Attaching the mechanism also affects the stabilization of the UAV. Hence, retuning of the PID controller was performed in order to correct the flight attitude of the UAV. This project successfully demonstrated the development of load carrying and releasing system which might serve as guidelines for other related future projects.